Effect of Problem Based Learning (PBL) Learning Strategies and Student Learning Styles on PKn Learning Outcomes of Grade V Students of Elementary School Experimental District of Kota Medan - Ramiyah Ramiyah; Reh Bungana Beru Perangin Angin; Yusnadi Yusnadi (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
The problem in this study is the low learning achievement of Pancasila and Citizenship Education. The purpose of this study was to determine the effect of learning styles on the Learning Outcomes of Pancasila and Citizenship Education. The type of research used is a 2x2 factorial design study. The population of this study amounted to 60 students and the sample was taken as a whole from the total population of 60 people consisting of 30 from class Va and 30 from class Vb Elementary School Experiment in Medan. Data collection techniques using questionnaires (questionnaires) and tests. Data analysis techniques used product moment correlation and Statistical Product and Service Solutions (SPSS) programs. The results obtained indicate that the value of students who have a visual learning style has a difference with students who have auditory learning styles with a sig value of 0.000 and a mean difference of 4.5756. Between students who have a visual learning style, have a significant difference with students who have kinesthetic learning styles, with a sig value of 0.002 and a mean difference of 4.4940. Between students who have auditory learning styles did not have a significant difference with students who have kinesthetic learning styles, with a sig value of 0.998 and a mean difference of only 0.815. The results showed that there was a significant effect between learning styles on the learning outcomes of Pancasila and Citizenship Education in the fifth grade students of SD Negeri Experiment City Medan